System robustness analysis in support of flood and drought risk management - Mens, M. J. P. (Deltares select series, 2015)
Floods and droughts have an increasing impact on societies worldwide. It is unlikely that the provision of flood protection infrastructure and reservoirs will eliminate this problem, especially as extreme events are expected to increase in probability and magnitude as a result of climate change. For this reason, the focus of water management has shifted to a risk-based approach in recent years; but this also has its limitations. This book examines system robustness as a new perspective on flood and drought risk management. The concept of robustness is familiar from other areas, such as engineer.